An Understanding of Urbanization and Political Challenges In India: a Research on Trends, Processes and Emerging Pattern: Examining the Impact of Urbanization on Economic Growth and Inequality in India (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The main objective of this paper is to analyze the recentpast trends and patterns of urbanization, urban economic growth, and urbanequity measured by urban poverty and inequality in India. In addition, it reviews thedifferent urban development policies and programmes which are undertaken indifferent Plan Periods in India.The analysis shows that higher rate of urbanization is associated with highereconomic growth, lower level of poverty and higher extent of inequality inurban India.Finally, the study suggests that Indian government needs to speed up theurbanization rate as it contributes higher share of national GDP by reducingurban poverty and inequality.